Design and synthesis of novel 3-hydroxy-cyclobut-3-ene-1,2-dione derivatives as thyroid hormone receptor ß (TR-ß) selective ligands - Raval, S.; Raval, P.; Bandyopadhyay, D.; Soni, K.; Yevale, D.; Jogiya, D.; Modi, H.; Joharapurkar, A.; Gandhi, Neha; Jain, M.; Patel, P. (Pergamon, 2008)
Design and synthesis of a novel 3-hydroxy-cyclobut-3-ene-1,2-dione derivatives are reported and their in vitro thyroid hormone receptor selectivity has been evaluated in the thyroid luciferase receptor assay. The 3-[3,5-dichloro-4-(4-hydroxy-3-isopropylphenoxy)-phenylamino]-4-hydroxy- cyclobut-3-ene-1,2-dione 21 has shown selectivity towards thyroid hormone receptor ß. © 2008 Elsevier Ltd. All rights reserved.